VD_FINDINFO AP / 2012 / 28 vom 12. September 2012 - VD Tribunal cantonal (2012)
TRANSACTION JUDICIAIRE, DÉCISION SUR FRAIS | 107 al. 1 let. c CPC (CH), 241 CPC (CH), 292 al. 1 let. b CPC (CH), 67 al. 2 TFJC (2010)